WAYS TO RESTORE THE PRODUCTION OF DRIED, FRESH PEAS - V.F. Pivovarov; N.S. Tsiganok (Овощи России)
The importance of production of fresh peas and methods of processing, technology for preparation of dried peas is highlighted in this article.